Pengaruh Musik Dalam Menurunkan Ansietas Pra-Tindakan Dental Pada Pasien di Poli Bedah Mulut Rumah Sakit PKU Muhammadiyah Surakarta - Pratama, Aprilian; , Dwi Kurniawati, S.KG, MPH; , drg. Naviatullaily Yarsiska (2016)
Background: Dental anxiety have a negative impact in improving oral health. High anxiety levels will cause failure on the treatment. Anxiety can increase blood pressure due to stimulation of the sympathetic nervous system which increases cardiac output and arteriolar vasoconstriction. The music is believed have an effect in decreasing anxiety. Objective: To determine the effect of music heard by patients before dental treatment toward dental anxiety patients. Methods: This study is a quasi-experimental design with samples was 35 peoples. Patient's anxiety levels were measured using the Modified Face Scales for Anxiety. Treatment by listening to the music with slow tempo (acoustic, pop, and instrumental pop) when waiting in the waiting room for 10 minutes. Changes in blood pressure that occurs between before and after listening to the music in measuring using digital sphygmomanometer. Processing techniques and data analysis with Paired T test. Results: The mean systolic blood pressure before is 121,94 mmHg and after is 119.06 mmHg. Statistical test results obtained by value p = 0.02 for systolic blood pressure. Mean diastolic blood pressure before is 85,09 mmHg and after is 84.51 mmHg. Test results for the diastolic blood pressure to get the value of p = 0.58. Ha if p <0.05, a decrease in systolic blood pressure can be accepted for p <0.05, while a decrease in diastolic blood pressure was not significant.Conclusion: Based on the results, it can be concluded that there is the influence of music on a decrease in systolic blood pressure and anxiety. The influence of music on a decrease in systolic blood pressure is very significant when compared with a decrease in diastolic blood pressure